Dinamika Perubahan Mangrove Menjadi Tambak dan Total Suspended Solid (TSS) di Sepanjang Muara Berau - Ety Parwati; Kadarwan Soewardi; Tridoyo Kusumastanto; Mahdi Kartasasmita; I Wayan Nurjaya (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
The mangrove conversion become fish pond, bareland or others has an impact in water quality. One of water quality parameter is Total Suspended Solid (TSS), increasing TSS means the rising in pollution.  Landsat remote sensing data with multi channels used in studying the dynamic of mangrove – fishpond change and TSS along the Berau waters. Several regions with its variation are used in that dynamic studying.  The TSS algorithm for Berau waters is TSS (mg/l) = 3.3238 * exp (34.099*Red Band) , Red band=the atmospheric reflectance band 2 validated with field data. The result study is the conversion of mangrove become fish pond has the strong indication in the rising TSS .